A New Model for Developing the Russian Far East. Issue 10 (3rd October 2017) - Zausaev, V.K.; Kruchak, N.A.; Bezhina, V.P.
Abstract : The article examines the processes of creating priority development areas (PDAs) in the Russian Far East, and describes their structure as well as their impact on the main macro-indicators of the subjects of the Far Eastern Federal District and the increased efficiency of its residents. It is concluded that in its present form the mechanism of the PDA will not increase the competitiveness of the Far East's economy. Finally, several prescriptions are made for improving PDAs.